Lung cancer - Guerreiro, Teresa (2020)
BACKGROUND/AIM: This study characterized lung cancer (LC) in Portugal, to capture sex differences, regional variation, and spatial distribution. PATIENTS AND METHODS: Variables: age, sex, vital status, region of residence, degree of urbanization, histologic types and stage at diagnosis. Spatial analyses conducted to identify high (HIC) and low incidence (LIC) clusters. RESULTS: In total, 11,642 cases were diagnosed (76.6% male, 23.4% female), with a similar mean age at diagnosis. There were 23,6% locally advanced and 58.4% metastatic disease cases, with 13.4% alive five years after diagnosis. Non-small-cell LC accounted for 77.3% of which 40.8% was adenocarcinoma and 22.7% was squamous cell carcinoma. Standardized incident rate (IR) was 37.5/105, 65.2/105 in males, and 15.7/105 in females, with four HIC (urban) clusters and four LIC (non-urban). CONCLUSION: This study highlighted the sex differences in incidence, mortality, histology, and geographic distribution of LC in Portugal. Considering the advanced stages and the poor overall survival, understanding sex and geographic differences is important for public health interventions.